Capital Structure with Company Size as a Moderating Variable in Food and Beverage Companies on the Indonesia Stock Exchange - Puteri Rafika Nur Alyaa; Dhani Ichsanuddin Nur (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to identify and analyse the relationship between business size and capital structure in the food and beverage industry in Indonesian public firms listed on the Indonesia Stock Exchange in the years 2028-2021. Three factors profitability, liquidity, and asset structure are evaluated here, with a moderating variable, namely company size. 28 food and beverage companies were sampled in this study using method of selecting samples on purpose. Two types of regression analysis, multiple and moderated, are used in this investigation. The findings of this research show that capital structure is influenced by profitability, liquidity, and asset structure, and that the impact of these factors is tempered by firm size.